Comparison of lip positions in ancient Buddhas with Japanese adults - Ioi Hideki; Nakata Shunsuke; Nakasima Akihiko; Counts Amy L. (Sciendo, 2023)
To compare the lip positions found in two ancient Buddha statues with the lip positions in contemporary Japanese adults.